Postural stability in vestibular neuritis: Age, disease duration, and residual vestibular function. (5th October 2013) - Fujimoto, Chisato; Egami, Naoya; Kinoshita, Makoto; Sugasawa, Keiko; Yamasoba, Tatsuya; Iwasaki, Shinichi
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis To assess the influence of factors that can affect postural instability in vestibular neuritis (VN). Study Design Retrospective data collection study. Methods Foam posturography was performed in 58 VN patients. We examined six variables: the velocity of movement of the center of pressure and the envelopment area in eyes closed/foam rubber condition, Romberg's ratios of velocity and area with foam rubber, and the foam ratios of velocity and area with eyes closed. Multiple regression analyses were performed to explore the relationship between these variables and the following independent variables: gender, age, canal paresis (CP) percentage, and disease duration. Results All six variables were positively associated with age, CP percentage, and a disease duration of 10 days or less (P < .05) except for Romberg's ratio of velocity with foam rubber, which was positively associated with CP percentage and a disease duration of 10 days or less (P < .05), but not with age (P > .05). Conclusions VN patients show poor postural performance, which is affected by age, residual vestibular function, and disease duration. Once a VN patient passes the acute phase of the vertigo attack, it is likely that age and residual vestibular function make a greater contribution to postural control. Level of Evidence 3b. Laryngoscope, 124:974–979, 2014